STUDI PERILAKU LINK PENDEK, LINK MENENGAH DAN LINK PANJANG PADA STRUKTUR BAJA SISTEM EBF - Jusuf Wilson Meynerd Rafael; Budi Suswanto (Journal of Civil Engineering, 2017)
The paper disccuses an analysis study on the design of Eccentrically Braced Frame (EBF) i.e. short link, intermediate link and long link) with K-Braces-type Split 1 floor. The analysis is performed by using ABAQUS with static monotonic loading in a single structure (frame). Each element of the frame is modeled as sholid 3D with connections to every element in the form of tie constraints and given fixed on each base of the column as a boundary condition. All three models of the frame has been analyzed in accordance with the AISC 2010 provisions and then compared the behavior of each of these models. The results indicate that the short link model considered in this study have on a higher over strength value and used as a proposed model when compared to intermediate link and long link model. It is stated by the failure mechanism as well, the failure is well-occurred in the short link condition than the other models